Role of Platelet Size Revisited—Function and Protein Composition of Large and Small Platelets - Handtke, Stefan; Steil, Leif; Palankar, Raghavendra; Conrad, Jane; Cauhan, Simran; Kraus, Luise; Ferrara, Myriam; Dhople, Vishnu; Wesche, Jan; Völker, Uwe; Greinacher, Andreas; Thiele, Thomas (Thrombosis and Haemostasis, 2019)
Epidemiological studies found an association between increased platelet size and the risk for thrombotic complications, but functional differences of large and small platelets remain poorly understood due to a lack of standardized protocols separating platelets with different size. We designed a protocol to separate large and small platelets from 15 mL whole blood. Separated large and small platelet fractions differed in mean platelet volume: 12.1 fl (10.3–13.8 fl) versus 7.7 fl (6.8–9.5 fl, p < 0.01), and forward scatter mean fluorescence intensity: 24.75 (19.9–30.9) versus 16.85 (11.3–20.6; p < 0.01). Similar fold differences were observed in cell diameter and plateletcrit. Large platelets express 30 to 50% more glycoprotein (GP) Ia, GPIb, GPIIIa, GPVI and P2Y12 on their membranes compared with small ones. Single large platelets covered a 50% larger area on a collagen surface. Adhesion to collagen was faster in large platelets compared with small ones indicating enhanced outside-in signal transduction in large platelets via collagen receptors. In contrast, integrin activation was more pronounced in small platelets after ADP stimulation. Proteome analysis revealed that 80 of the 894 proteins quantified differed in abundance: ADP-ribosylation factor 1/3, guanosine triphosphate-binding protein SAR1a, Voltage-dependent anion-selective channel protein 3 and guanylate cyclase soluble sub-unit α-3 were higher abundant in large, whereas immunoglobulins, haptoglobin, hemopexin, α-1-antitrypsin, serotransferrin and vitronectin were more abundant in small platelets. We conclude that some functions and the protein composition of large and small platelets differ, which cannot only be explained by the size difference. Our data suggest different functional roles of large and small platelets.
Keywords: platelet physiology; platelet size; platelet function